2001
DOI: 10.1074/jbc.m008311200
|View full text |Cite
|
Sign up to set email alerts
|

The GLFG Regions of Nup116p and Nup100p Serve as Binding Sites for Both Kap95p and Mex67p at the Nuclear Pore Complex

Abstract: Our previous studies have focused on a family of Saccharomyces cerevisiae nuclear pore complex (NPC) proteins that contain domains composed of repetitive tetrapeptide glycine-leucine-phenylalanine-glycine (GLFG) motifs. We have previously shown that the GLFG regions of Nup116p and Nup100p directly bind the karyopherin transport factor Kap95p during nuclear protein import. In this report, we have further investigated potential roles for the GLFG region in mRNA export. The subcellular localizations of green fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 52 publications
6
108
0
Order By: Relevance
“…2, lane 3). Our previous studies have shown that the anti-GFP antibodies are specific only for the GFP-tagged proteins (29). Taken together, these results strongly suggest that Gfd1 and Nab2 associate in a complex in vivo.…”
Section: Nab2 Exists In a Complex With Gfd1 In Vivo-supporting
confidence: 59%
See 2 more Smart Citations
“…2, lane 3). Our previous studies have shown that the anti-GFP antibodies are specific only for the GFP-tagged proteins (29). Taken together, these results strongly suggest that Gfd1 and Nab2 associate in a complex in vivo.…”
Section: Nab2 Exists In a Complex With Gfd1 In Vivo-supporting
confidence: 59%
“…The bound protein was eluted with column buffer containing 10 mM maltose. MBP-Gle2 (kindly provided by L. Strawn) was purified as described previously (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional evidence that transport receptors rely on distinct FG repeats and/or nucleoporins comes from yeast where mutations or over expression of individual nucleoporins can affect the translocation of particular transport receptors without affecting the movement of others (Bastos et al, 1996;Belgareh et al, 1998;Balasundaram et al, 1999). Mex67p, the Tap homologue in Saccharomyces cerevisiae, and Kap95p bind distinct repeats within Nup116 (Strawn et al, 2001). Moreover, the interaction between Tap and Nup98 is confined to a subset of the GLFG repeats in Nup98 (Blevins et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 3500 FG repeats are distributed throughout each NPC (Strawn et al, 2004). Recent evidence suggests that transport receptors interact with distinct subsets of FG repeats (Clarkson et al, 1997;Damelin and Silver, 2000;Strawn et al, 2001;Blevins et al, 2003;Strawn et al, 2004). This could provide part of the basis for coordinating bidirectional flow of traffic through the NPC, which is estimated to approach 1000 molecules per second (Ribbeck and Gorlich, 2001).…”
Section: Introductionmentioning
confidence: 99%